2019
DOI: 10.1177/0892705719886011
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cross-linked PVC-g-(St-MA) copolymer/organoclay nanocomposites and investigation of chemical characteristics, morphology, thermal, and mechanical properties

Abstract: The goal of this work is to investigate the effect of incorporating organoclays on the cross-link structure, morphology, and thermomechanical properties of cross-linked organoclay/polyvinyl chloride grafted with styrene and maleic anhydride (PVC- g-(St-MA)) copolymer nanocomposites (CPN). Cloisite30B (C30B) and Cloisite15A (C15A) organoclays were used for the preparation of cross-linked PVC- g-(St-MA) nanocomposites by the solution mixing route. The nanoclay content in nanocomposites varied from 0.2 wt% to 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Stirring, shear mixing, and ultrasonication are the agitation forces that facilitate clay dispersion in the polymer solution. In the final step, the solvent is removed, leading to the reassembling of the polymer-intercalated clay and the nanocomposite formation [ 49 , 95 , [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] ]. It is noteworthy that the solvent evaporation rate is critical to the quality of the composite films.…”
Section: Manufacture Of Pvc-clay Composite and Nanocompositementioning
confidence: 99%
See 1 more Smart Citation
“…Stirring, shear mixing, and ultrasonication are the agitation forces that facilitate clay dispersion in the polymer solution. In the final step, the solvent is removed, leading to the reassembling of the polymer-intercalated clay and the nanocomposite formation [ 49 , 95 , [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] ]. It is noteworthy that the solvent evaporation rate is critical to the quality of the composite films.…”
Section: Manufacture Of Pvc-clay Composite and Nanocompositementioning
confidence: 99%
“…The position, shape, and intensity of XRD peaks reveal the structural variation of the nanocomposites. For example, complete delamination of clay is reflected by the disappearance of XRD peaks [ 121 ], while intercalation results in the shift of XRD peaks to lower angles and a decrease in peak intensity [ 49 , 110 , 113 , 122 , 123 ]. Fig.…”
Section: Characterization Of Pvc-clay Composite and Nanocompositementioning
confidence: 99%
“…This salt can easily release HCl gas at high temperatures and results in self-catalyzed degradation of PVC. [7][8][9] Therefore, introducing a formulation for improving thermal stability of PVC/clay nanocomposites has become a challenging topic during the past several decades. Zheng et al used some stabilizers including organotin, calcium/zinc, barium/zinc, and an epoxy co-stabilizer and showed that the combination of the organotin stabilizer and the epoxy co-stabilizer was effective for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…1 Low price, high processability with additive materials, self-extinguishability, and great fire and chemical resistances are some of the excellent features of PVC which lead it to extensively be used in various fields, such as automobile, packing, and pipe preparation. 2,3 Among PVC-based productions, PVC foams, in addition to the aforementioned properties, possess high strength-to-weight ratios and low water absorption content. 4 PVC foams are widely employed as a core in sandwich-structured composites in different applications, including wind energy, aerospace, transportation and industrial applications, which require damage tolerance and weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…1315 One of the most commonly used nanofillers in the preparation of nanocomposite C-PVC foams is the exfoliated and intercalated layers of montmorillonite layered silicate (MLS), such as montmorillonite (MMT) clay with layered silicate structure, which belongs to dioctahedral smectite. 2,16 Due to their high aspect ratio, the layered silicate sheets have a large contact surface with foam matrix which improves C-PVC’s performance. The dispersion and delamination degrees of layered silicate directly control their effectiveness on C-PVC’s properties and the most ideal state could be achieved by a uniform distribution of exfoliated structure throughout the foam matrix.…”
Section: Introductionmentioning
confidence: 99%